(untitled) (Web of Teachers: Inderscience Research, 2023)
This article highlights the place and role of the concept of tolerance in the history of Western countries and today in the process of globalization. In addition to the formation of a tolerant worldview in the mind of the Western society, the essence of the concept of tolerance is explained from their own points of view.